Abdominal obesity, metabolic syndrome in type 1 diabetic children and adolescents - Anna Gadzicka; Anna Kozera; Joanna Szlawska; Iwona Pietrzak; Agnieszka Szadkowska; Wojciech Młynarski (Pediatric Endocrinology, Diabetes and Metabolism)
Introduction: The rapid rising prevalence of childhood obesity is related to the increased risk of cardiovascular morbidities. The type 1 diabetic patients are the group at special risk of macroangiopathy. The aim of the study was to estimate the prevalence of abdominal obesity in type 1 diabetic children compared to the general population, and to estimate the prevalence of metabolic syndrome diagnosed according to IDF criteria in type 1 diabetic children and adolescents. Material and methods: 163 patients with type 1 diabetes mellitus (91 male) aged from 10 to 18 years were included into the study. The diabetes duration ranged from 0.5 to 15.2 years. The height, weight, waist circumference, body fat and blood pressure were measured. HbA1c and plasma lipids concentrations were examined. Body mass index, waist/height ratio (WHtR) and daily dose of insulin were calculated. Estimated glucose disposal rate (eGDR) as indicator of insulin resistance was calculated according to own formula. Results: Abdominal obesity diagnosed as WHtR >0.5 was found in 19 patients (11.7%, CI95% 6.7-16.6). Associations between WHtR and HbA1c (r=0.18; p=0.027), cholesterol-HDL (r=-0.22; p=0.004), systolic (β=0.37; p <0.001) and diastolic blood pressure (β=0.19, p=0.046) and Body Fat% (r=0.59; p <0.001) were observed. The prevalence of abdominal obesity in diabetic children was higher than in the general population (12.2 vs. 6.8%; p=0.030). The metabolic syndrome was found in 12 individuals (7.4%, CI95% 3.4-11.4). Patients with metabolic syndrome were older (16.6 vs. 14.7 years; p=0.006) and their Body Fat% was higher (21 vs. 30%; p <0.001) compared to patients not fulfilling the metabolic syndrome criteria. Conclusions: The prevalence of abdominal obesity in diabetic children is higher than in the general population. WHtR is associated with components of metabolic syndrome. Patients with metabolic syndrome are older and they are characterized by increased body fat.